Commentary—The Desegregation Dilemma: A Vote for Voluntarism - Frank I. Goodman (Washington University Law Quarterly, 1979)
I wish to add my thoughts on what the Court should have done-and yet should do-to resolve the painful dilemmas posed by the desegregation issue.
Keywords: Public schools; Desegregation